Reaction Mechanisms of Layered Lithium‐Rich Cathode Materials for High‐Energy Lithium‐Ion Batteries - Zhao, Shuoqing; Yan, Kang; Zhang, Jinqiang; Sun, Bing; Wang, Guoxiu (Angewandte Chemie International Edition, 2021)
Layered lithium‐rich cathode materials have attracted extensive interest owing to their high theoretical specific capacity (320–350 mA h g−1). However, poor cycling stability and sluggish reaction kinetics inhibit their practical applications. After many years of quiescence, interest in layered lithium‐rich cathode materials is expected to revive in answer to our increasing dependence on high‐energy‐density lithium‐ion batteries. Herein, we review recent research progress and in‐depth descriptions of the structure characterization and reaction mechanisms of layered lithium‐rich manganese‐based cathode materials. In particular, we comprehensively summarize the proposed reaction mechanisms of both the cationic redox reaction of transition‐metal ions and the anionic redox reaction of oxygen species. Finally, we discuss opportunities and challenges facing the future development of lithium‐rich cathode materials for next‐generation lithium‐ion batteries. Layered lithium‐rich materials are promising cathode materials for the development of next‐generation high‐energy‐density lithium‐ion batteries. Understanding the principles of the performance degradation mechanisms is a prerequisite for progress in this area. In this Minireview, recent research on the material structure and reaction mechanisms of layered lithium‐rich manganese‐based cathode materials is discussed.